Bananas, beaches and bases: making feminist sense of international politics - Enloe, Cynthia H. (University of California Press, 2014)
In this brand new radical analysis of globalization, Cynthia Enloe examines recent events—Bangladeshi garment factory deaths, domestic workers in the Persian Gulf, Chinese global tourists, and the UN gender politics of guns—to reveal the crucial role of women in international politics today. With all new and updated chapters, Enloe describes how many women's seemingly personal strategies—in their marriages, in their housework, in their coping with ideals of beauty—are, in reality, the stuff of global politics. Enloe offers a feminist gender analysis of the global politics of both masculinities and femininities, dismantles an apparently overwhelming world system, and reveals that system to be much more fragile and open to change than we think.
Keywords: approches et analyses; cours; discipline; histoire et politique; intersectionnalité; inégalités; pol5480; politique internationale; premier cycle; ressource en ligne; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques; travail

The SAGE handbook of feminist theory - Evans, Mary (SAGE reference, 2014)
At no point in recorded history has there been an absence of intense, and heated, discussion about the subject of how to conduct relations between women and men. This Handbook provides a comprehensive guide to these omnipresent issues and debates, mapping the present and future of thinking about feminist theory. The chapters gathered here present the state of the art in scholarship in the field, covering: Epistemology and marginality; Literary, visual and cultural representations; Sexuality; Macro and microeconomics of gender; Conflict and peace. The most important consensus in this volume is that a central organizing tenet of feminism is its willingness to examine the ways in which gender and relations between women and men have been (and are) organized. The authors bring a shared commitment to the critical appraisal of gender relations, as well as a recognition that to think ‘theoretically’ is not to detach concerns from lived experience but to extend the possibilities of understanding. With this focus on theory and theorizing about the world in which we live, this Handbook asks us, across all disciplines and situations, to abandon our taken-for-granted assumptions about the world and interrogate both the origin and the implications of our ideas about gender relations and feminism. It is an essential reference work for advanced students and academics not only of feminist theory, but of gender and sexuality across the humanities and social sciences.
Keywords: approches et analyses; corps; cours; discipline; har4600; histoire et politique; intersectionnalité; outils; ouvrages de références; philosophie; phénoménologie; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences de la gestion; sciences humaines; sciences sociales; sex1911; thématiques; violences; économie; épistémologie; études féministes

Sur l’indivisibilité de la justice sociale ou Pourquoi le mouvement féministe québécois ne peut faire l’économie d’une analyse intersectionnelle - Pagé, Geneviève (Nouvelles pratiques sociales, 2014)
En partant du concept d’indivisibilité de la justice, cet article se penche sur la pertinence des théories de l’intersectionnalité des oppressions dans le contexte du féminisme québécois francophone pour démontrer 1) l’existence d’une protothéorie de l’intersectionnalité dans le féminisme radical des années 1970 au Québec et 2) que les féministes québécoises d’aujourd’hui sont bien placées pour proposer une synthèse entre l’approche intersectionnelle en provenance des États-Unis et le matérialisme français. Cette démonstration permettra au passage de récuser deux accusations fallacieuses au sujet de l’approche intersectionnelle, soit qu’elle est postmoderne et source de fragmentation du mouvement féministe.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; féminisme matérialiste; histoire et politique; intersectionnalité; justice sociale; militance; mouvements féministes; privilèges; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques